UKRAINIAN SCIENTIST PROFESSOR S. P. TYMOSHENKO (1881–1950) - Oleksandr Utkin (Київські історичні студії)
The article reflects the main periods of the life of the Ukrainian scientist, engineer, professor of architecture Sergiy Tymoshenko, namely his public, political, educational and scientific activity since his childhood and adolescence, study at the Institute of Civil Engineers in St. Petersburg. His activity as an architect in Volyn, Kyiv and Kharkiv, the construction projects he has created in these regions, are analysed. He tried to recreate the Ukrainian national style of construction — the Cossack Baroque. As a supporter of Ukrainian independence, he took an active part in the development of its statehood and during 1919–1920 he worked as the Minister of Roads in the governments of the UNR. After the defeat of the national liberation struggle Tymoshenko became an emigrant, where he was engaged in the development and implementation of construction projects, later he worked as a teacher in the Ukrainian Academy of Economics and the Ukrainian Studio of Plastic Arts (Academy). Together with the other representatives of the intelligentsia, he led a public activity, defending Ukrainian spiritual values. After moving to the USA, Sergiy Tymoshenko worked as an architect.